ESTABLISHING PUBLIC CONSENSUS THROUGH DEVELOPING SPATIAL MULTIMEDIA SYSTEM TOWARDS SMART GOVERNANCE IN MANAGING CITYSCAPE PLANNING - Santosa, Herry; Fauziah, Nur (PEOPLE: International Journal of Social Sciences, 2019)
The rapid development of information technology leads to the changes of the urban management system demanding the utilization of the smart city concept which aims to provide an environment for the community that is efficient, sustainable and secure, with the use of ICT (Information and Communications Technology). This paper utilized smart governance concept as one aspect of a smart city to improve and develop community participation in the visual quality control of urban spaces that meet the social aspects, economic efficiency and biological health of the community through visual quality evaluation activities on city space corridors. The development of spatial multimedia support system is one of the current development in urban planning that associated with public engagement. The objective of the study is to develop a scenario of the 3D spatial multimedia system as a Decision Planning Support System for structuring street corridor landscape based on 3D Interactive Simulation System. Through the scenario of interactivity development, 3D visualization in the virtual environment is expected to be efficient as well as supporting the development of the effectiveness of decision-making system in the evaluation of visual comfort quality in the streetscape.